Demographically adjusted norms for the Trail Making Test in native Spanish speakers: Results from the neuropsychological norms for the US-Mexico border region in Spanish (NP-NUMBRS) project. Issue 2 (6th February 2021) - Suarez, Paola A.; Díaz-Santos, Mirella; Marquine, Maria J.; Kamalyan, Lily; Mindt, Monica Rivera; Umlauf, Anya; Heaton, Robert K.; Grant, Igor; Cherner, Mariana
Abstract: Objective: Despite the wide use of the Trail Making Test (TMT), there is a lack of normative data for Spanish speakers living in the USA. Here we describe the development of regional norms for the TMT for native Spanish speakers residing in the Southwest Mexico-Border Region of the USA. Method: Participants were 252 healthy native Spanish speakers, 58% women, from ages 19 to 60, and ranging in education from 0 to 20 years, recruited in San Diego, CA and Tucson, AZ. All completed the TMT in Spanish along with a comprehensive neuropsychological test battery as part of their participation in the Neuropsychological Norms for the US–Mexico Border Region in Spanish (NP-NUMBRS) project. Univariable and interactive effects of demographics on test performance were examined. T-scores were calculated using fractional polynomial equations to account for linear and any non-linear effects of age, education, and sex. Results: Older age and lower education were associated with worse scores on both TMT A and B. No sex differences were found. The newly derived T-scores showed no association with demographic variables and displayed the expected 16% rates of impairment using a −1 SD cut point based on a normal distribution. By comparison, published norms for English-speaking non-Hispanic Whites applied to the current data yielded significantly higher impairment for both TMT A and B with more comparable rates using non-Hispanic African Americans norms. Conclusions: Population-specific, demographically adjusted regional norms improve the utility and diagnostic accuracy of the TMT for use with native Spanish speakers in the US-Mexico Border region.